Measuring Tiktok Shop Service Quality Using The E-ServQual Method And Importance Performance Analysis (IPA) Method - Marlindawati, Marlindawati; Sahfitri, Vivi; Rosalinda, Rosalinda (Journal of Information System and Informatics, 2025)
Utilizing online shop services is an example of applying technology that aims to increase product sales, one of which is TikTok Shop. This research aims to measure the quality of service provided by TikTok Shop in order to offer appropriate recommendations for improving service features and other aspects. The method used is e-servqual, which includes variables such as efficiency, compliance, reliability, privacy, responsiveness, compensation, and contact which are used to identify service quality factors that require repair, maintenance, or improvement. The Importance Performance Analysis (IPA) method is used to assess the performance of services provided to consumers compared to desired expectations. The results of measurement research using the e-ServQual method show a satisfaction index of 0.925274, which means TikTok Shop users are very satisfied, because the service quality score is close to 1. Measurements using the IPA method reveal three attributes that require performance improvement. These three attributes have the highest priority for improved to increase user satisfaction. Additionally, seven attributes can be retained because their performance exceeds the user's importance level. It is hoped that the results of this research can provide valuable contributions or insights for relevant stakeholders.